TRICHINELLOID EGGS (NEMATODA) IN A SOUTHERN GIANT PETREL (MACRONECTES GIGANTEUS, PROCELLARIFORMES: PROCELLARIIDAE) FROM SOUTHERN BRAZIL - Brandão, Martha (2008)
During the winter of 2003 the seabird (Macronectes giganteus) was found scrawny at Atlântida Sul beach, north coast of State of Rio Grande do Sul – Brazil. Fresh fecal sample were collected at CECLIMAR (Centro de Estudos Costeiros, Limnológicos e Marinhos da Universidade Federal do Rio Grande do Sul) rehabilitation center and fixed in Railliet & Henry solution. Using spontaneous sedimentation technical to helminth eggs, 10 slides were obtained. All eggs found were of one species of Trichinelloidea superfamily (n=82). The eggs found here, are a new record of helminth parasite of Petrel.